Powder Pressed Cuprous Iodide (CuI) as A Hole Transporting Material for Perovskite Solar Cells - Uthayaraj, S.; Karunarathne, D.G.B.C.; Kumara, G.R.A.; Murugathas, T.; Shivatharsiny, R.; Rajapakse, R.M.G.; Ravirajan, P.; Velauthapillai, D. (Materials, 2019)
Abstract: This study focuses on employing cuprous iodide (CuI) as a hole-transporting material (HTM) in fabricating highly efficient perovskite solar cells (PSCs). The PSCs were made in air with either CuI or 2,20 ,7,70 -Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,90 -spirobifluorene (spiro-OMeTAD) as HTMs. A simple and novel pressing method was employed for incorporating CuI powder layer between perovskite layer and Pt top-contact to fabricate devices with CuI, while spiro-OMeTAD was spin-coated between perovskite layer and thermally evaporated Au top-contact to fabricate devices with spiro-OMeTAD. Under illuminations of 100 mW/cm2 with an air mass (AM) 1.5 filter in air, the average short-circuit current density (JSC) of the CuI devices was over 24 mA/cm2 , which is marginally higher than that of spiro-OMeTAD devices. Higher JSC of the CuI devices can be attributed to high hole-mobility of CuI that minimizes the electron-hole recombination. However, the average power conversion efficiency (PCE) of the CuI devices were lower than that of spiro-OMeTAD devices due to slightly lower open-circuit voltage (VOC) and fill factor (FF). This is probably due to surface roughness of CuI powder. However, optimized devices with solvent-free powder pressed CuI as HTM show a promising efficiency of over 8.0 % under illuminations of 1 sun (100 mW/cm2 ) with an air mass 1.5 filter in air, which is the highest among the reported efficiency values for PSCs fabricated in an open environment with CuI as HTM.
Keywords: Perovskite solar cells; Hole-transporting material; Powder pressing; Cuprous iodide; CuI; Spiro-OMeTAD; Air stable